Visualizing unique vasculature in the human spleen with two- and three-dimensional imaging - Minkkinen, Emilia (My University, 2025)
The spleen is the largest secondary lymphoid organ in the human body. It has significant roles in homeostasis and systemic immunity. In addition, the organ constantly filters blood eliminating pathogens and old red blood cells from the circulation. According to research, patients lacking the spleen are at higher risk of infection due to encapsulated bacteria, viruses and parasites. Surprisingly, the existence of lymphatic vessels is undefined in the human spleen. According to current knowledge, lymphocytes enter the organ via blood circulation. Recent research by Kalucka et al. reveals that the mouse spleen lacks lymphatic markers, as visualized my single-cell RNA sequencing. Nevertheless, striking anatomical differences between the mouse and human spleen have been discovered and therefore current information that relies on mouse data should be questioned and researched further. The aim of this study was to visualize the unique vasculature of the human spleen with two- and three-dimensional imaging techniques. With patient samples acquired from the Turku University Hospital, we were able to visualize novel structures of the blood and lymphatic vasculature. We used common methods of immunohistochemistry and tissue clearing to get desired results. Tissue clearing enabled us to use thicker samples, which provided more reliable information of the structures in relation to each other. In this study we were able to visualize lymphatic like-vessels utilizing lymphatic valves as proof. In addition, a novel molecule known as MAdCAM-1, was imaged in the blood vasculature of the spleen. MAdCAM-1 positive vessels connect to LYVE-1 positive vessels, which suggests that MAdCAM-1 could have a functional role in lymphocyte trafficking in the organ. All in all, this study provides critical information based entirely on human material and can be used in further research to discover the unknown functions of this enigmatic organ.

Perna on ihmisen suurin toissijainen lymfaattinen elin. Sillä on merkittäviä tehtäviä elimistön homeostaasin ja systeemisen immuniteetin ylläpitämisessä. Perna siivilöi jatkuvasti verta hävittäen taudinaiheuttajia sekä vanhoja punasoluja verenkierrosta. Tutkimusten mukaan potilaat, joilta puuttuu perna, ovat suuremmassa vaarassa saada bakteeri-,virus- ja parasiitti-infektioita. Yllättäen imusuonten olemassaoloa ei ole pystytty osoittamaan ihmispernassa. Nykyisen oletuksen mukaan imusolut kulkevat elimeen veren mukana. Kalucka ym. huomasivat tutkimuksessaan, että imusuoniston merkkiaineet puuttuvat täysin hiiren pernasta. On kuitenkin tiedossa, että hiiren ja ihmisen pernassa on paljon rakenteellisia eroja, joiden takia käsitystä imusuonten puuttumisesta ei voida suoraan soveltaa ihmispernaan. Täten suoniston tarkempi selvittely ihmisnäytteitä hyödyntäen on ensisijaisen tärkeää. Tämän tutkimuksen tarkoituksena oli visualisoida pernan ainutlaatuista suonistoa kaksi- ja kolmiulotteisilla kuvantamismenetelmillä. Turun yliopistollisesta keskussairaalasta saatujen ihmispernanäytteiden avulla onnistuttiin havainnollistamaan veri- ja imusuoniston rakenteita immunohistokemiallisia menetelmiä hyödyntäen. Lisäksi pernakudos tehtiin läpinäkyväksi, mikä mahdollisti normaalia paksumpien näytteiden kuvantamisen. Paksummat näytteet antoivat entistä luotettavampaa tietoa suoniston rakenteista. Tutkimuksen tärkeimpänä löydöksenä oli imusuonten kaltaisten suonirakenteiden visualisointi ihmispernassa. Tämän lisäksi MAdCAM-1-molekyylin havainnollistaminen pernan verisuonistossa ja sen yhteys LYVE-1 positiiviseen suonistoon oli merkittävä tulos. MAdCAM-1-molekyylillä tiedetään olevan tärkeä rooli imusolujen kuljettamisessa muissa kudoksissa, kuten suolistossa, mikä voisi viitata vastaavanlaiseen tehtävään myös pernassa. Kaiken kaikkiaan, tätä ainutlaatuista työtä voidaan hyödyntää osana ihmispernan rakenteen ja toiminnan laaja-alaista tutkimusta.
Keywords: spleen,lymphatic vasculature,blood vasculature,MAdCAM-1